Markers of Procoagulant Imbalance in Patients with Inherited Thrombophilic Syndromes - Mannucci, P M; Tripodi, A; Bottasso, B; Baudo, F; Finazzi, G; Stefano, V De; Palareti, G; Manotti, C; Mazzucconi, M G; Castaman, G (Thrombosis and Haemostasis, 1992)
In 107 asymptomatic and untreated patients with inherited syndromes associated with thrombophilia (antithrombin III, protein C and protein S deficiencies), we compared in parallel two plasma peptides which reflect activation of the common coagulation pathway: the prothrombin fragment 1 + 2 (F1+2) and fibrinopeptide A (FPA). Both F1+2 and FPA were measured with simple, commercially available ELISA methods. High levels of F1+2 or FPA were found in about one fourth of the patients as a whole. When patients were divided according to the type of inherited thrombophilie syndrome, it appeared that F1+2 was more frequently elevated in protein C and protein S deficiencies than in antithrombin deficiency; and that, in general, it was no more frequently elevated than FPA. Although our data confirm the existence of a procoagulant imbalance in inherited thrombophilie syndromes due to defects of natural anticoagulant proteins, they do not confirm that such imbalance can be more frequently diagnosed by measuring F1+2 levels, particularly in patients with antithrombin deficiency.